Phase-amplitude coupled persistent theta and gamma oscillations in rat primary motor cortex in vitro - ÖZKAN, MAZHAR (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In vivo, theta (4-7 Hz) and gamma (30-80 Hz) neuronal network oscillations are known to coexist and display phase-amplitude coupling (PAC). However, in vitro, these oscillations have for many years been studied in isolation. Using an improved brain slice preparation technique we have, using co-application of carbachol (10 mu M) and kainic acid (150 nM), elicited simultaneous theta (6.6 +/- 0.1 Hz) and gamma (36.6 +/- 0.4 Hz) oscillations in rodent primary motor cortex (M1). Each oscillation showed greatest power in layer V. Using a variety of time series analyses we detected significant cross-frequency coupling in 74% of slice preparations. Differences were observed in the pharmacological profile of each oscillation. Thus, gamma oscillations were reduced by the GABAA receptor antagonists, gabazine (250 nM and 2 mu M), and picrotoxin (50 mu M) and augmented by AMPA receptor antagonism with SYM2206 (20 mu M). In contrast, theta oscillatory power was increased by gabazine, picrotoxin and SYM2206. GABA(B) receptor blockade with CGP55845 (5 mu M) increased both theta and gamma power, and similar effects were seen with diazepam, zolpidem, MK801 and a series of metabotropic glutamate receptor antagonists. Oscillatory activity at both frequencies was reduced by the gap junction blocker carbenoxolone (200 mu M) and by atropine (5 mu). These data show theta and gamma oscillations in layer V of rat M1 in vitro are cross-frequency coupled, and are mechanistically distinct. The development of an in vitro model of phase-amplitude coupled oscillations will facilitate further mechanistic investigation of the generation and modulation of coupled activity in mammalian cortex. (C) 2017 The Authors. Published by Elsevier Ltd.
Keywords: Neuronal network oscillations; M1; Theta; Gamma; Phase amplitude coupling; PARVALBUMIN-POSITIVE INTERNEURONS; NITRIC-OXIDE SYNTHASE; ENTORHINAL CORTEX; HIPPOCAMPAL-FORMATION; NETWORK OSCILLATIONS; RECEPTOR ACTIVATION; BEHAVING RAT; NEURONAL OSCILLATIONS; CORTICAL OSCILLATIONS; SOMATOSENSORY CORTEX